An Emploees Wage, Salary in Islamic Jurisprudence - Ismaeel Salih Hamzah (My University, 2010)
Through this research the worker can recognize many of his rights, including the right of remuneration. The employer can also recognize his responsibility for the payment of remuneration, which are considered the most important elements that tie the employer and the employee. So, first, the research explores the status of the worker and its importance in Islam, and the relationship between wage and employment. As a rule there is no reward without work. However, the outlook is not purely a materialistic element. The worker is Islam is viewed as a human being who should be provided with what he needs and should take his right completely, as compared to other doctrines that look in an inferior way to the worker. Then, the research talked about the legality of pay, their conditions, their types and their importance for the individual, the family and society. Remuneration is considered legal as documented in the holy Quran and Sunnah of the prophet Mohammad (mpbuh) and the consensus of Imams. This should be done under certain conditions as gained through a legal way, and be gained for actual work. The reason for the requirement of these conditions is to avoid disagreement. By these conditions every dispute could be avoided. Moreover, this study talks about the types of pay, as compensation increases, grants, incentives and how to calculate pay. Remuneration may be calculated by taking time into consideration or production or according to time and production. Protecting remuneration is one of the things that should protect them from reduction in value. So paying should be done by paying wages in the local currency, and the value of wage should be considered seriously. Workers should not be obligated to purchase things that are not of first importance to them. Then I talked about wage determination, from the point of view of different Imams, and the legality of Imams in identifying the factors that relate to wage-setting as the environment, the nature of the labor market, and how wages are paid, delayed or accelerated. Working hours and how wages are determined by representatives of workers, employers and under certain conditions as minimum and maximum wage rate that the employer does not go beyond are discussed later in this section. Among things that threaten wages and causes harm to workers and the community is the reduction of the value of wages which is caused by many factories as price increases, loans, low savings, migration, and increased rates of poverty and unemployment. Proposed solutions to these may be increasing production, more exchange rate stability, fair taxes, wage increases, supporting goods and food supplies, and mainly and finally the rule of Islamic morality. As well as wages have declined in value, whether in whole or eroded by certain way to be repaid.

من خلال هذا البحث يستطيع العامل أن يتعرف على كثير من الأمور التي له، ومنها حقه في الأجر، وصاحب العمل يستطيع أن يتعرف ما عليه وهو دفع الأجر, والأجر من أهم العناصر التي يرتبط بها صاحب العمل والعامل. لذا كان البحث أولاً عن مكانة العامل وأهميته في الإسلام، مقارنا ذلك بنظرة المذاهب الأخرى إلى العامل، وما آلت إليه النظريات الأرضية من نتائج. ثم الحديث عن مشروعية الأجر وشروطه وأنواعه وأهميته بالنسبة للفرد والأسرة والمجتمع. فالأجر مشروع من خلال الكتاب الكريم والسنة المطهرة والإجماع وبقية المصادر التشريعية الأخرى، وله شروط لا بد من توفرها ليكون صحيحاً، كأن يكون الأجر من مال حلال متقوّم، وأن يكون مقابل عمل مشروع يستفاد منه، ومن أسباب اشتراط الشروط الخلاف الذي قد يحدث؛ فبالشروط يرتفع كل خلاف قد ينشأ. وكذلك الحديث عن أنواع الأجر، كأجر المثل والزيادات والتعويضات والمنح والمحفزات وطريقة احتساب الأجر وكيف يكون ذلك، فالأجر قد يحسب بناءً على الزمن أو الإنتاج أو حسب الزمن والإنتاج، وحماية الأجر من الأمور التي قد تؤثر عليه بالنقص، وذلك بدفع الأجر بالعملة المتداولة، وأن تكون قيمة الأجر هي المعتبرة، وعدم إلزام العامل بشراء ما يحتاج له من جهة معينة، ثم الحديث عن تحديد الأجور من خلال مشروعية تحديدها وخلاف الفقهاء في ذلك والعوامل التي لها علاقة بتحديد الأجور؛ من بيئة وطبيعة لسوق العمل، وكيفية دفع الأجر؛ مؤجّلاً أو معجّلاً أو منجّماً (موزعا على أوقات معلومة)، وساعات العمل، وتحدَّد الأجور من قبل ممثلين عن العمال وأرباب العمل وعن ولي الأمر، ويكون ذلك في ظلِّ ظروفٍ غير طبيعية، ويكون للأجر عادة حدٌ أدنى وحدٌ أعلى لا يتم تجاوزهما. ومن الأمور المهمة التي تناولها البحث كذلك، زكاة الأجور، وانخفاض قيمتها، وأسباب ذلك كثيرة منها ارتفاع الأسعار وما يصيب النقود من رخص، وكذلك القروض الربوية، فيكون لهذه الأمور آثارٌ سلبية على المجتمع تتمثل في: تأثُّر عملية التنمية سلباً، وضعف الادّخار، والهجرة، وزيادة معدلات الفقر والبطالة. وكذلك الأجور المستحقة في الذّمة وقد انخفضت قيمتها، سواءً تآكلت بشكلٍ كاملٍ أو بنسبةٍ معينةٍ كيف يكون تسديدها.
أجر العامل في الفقه الإسلامي